Phosphodiesterase-5 inhibitors: Raynaud's and beyond - Sanat Phatak; Sajal Ajmani; Vikas Agarwal; Durga Prasanna Misra (Indian Journal of Rheumatology)
Phosphodiesterases (PDE) are a group of ubiquitously present enzymes involved in regulation of various cellular pathways. PDE5 acts to metabolize cyclic guanosine monophosphate (GMP). The various PDE5 inhibitors available are sildenafil, tadalafil, vardenafil, and mirodenafil. We shall discuss the roles of various PDE5 inhibitors in rheumatic diseases. PDE5 inhibitors prevent degradation of cyclic GMP; hence, they have vasodilatory properties which render them useful in the management of secondary Raynaud's phenomenon. They have also demonstrated efficacy in the healing of digital ulcers in systemic sclerosis and potentially prevent the formation of new digital ulcers. Their vasodilatory property has also been utilized in the management of pulmonary arterial hypertension, wherein their ability to favorably affect hemodynamics of a pressure-overloaded right heart is beneficial. Recent evidences have suggested a potential antifibrotic role of these agents, and studies in idiopathic pulmonary fibrosis and systemic sclerosis-associated interstitial lung disease hold promise for future exploration of these agents for these indications.